Microservice-Aware CI/CD Pipelines: Dependency Graphs, Build Isolation, And Deployment Orchestration - Pathik Bavadiya (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Because of the growing complexity of microservice architectures, continuous integration and continuous delivery pipelines need to be efficient, dependable, and robust in order to maintain rapid software delivery cycles. For the purpose of optimizing microservice-aware continuous integration and continuous delivery pipelines, this study studied the integration of dependency graphs, build isolation, and deployment orchestration as optimization methodologies. In this study, a mixed-method research methodology was utilized, which included both experimental evaluation through the use of a simulated environment consisting of twenty microservices and qualitative insights from fifteen DevOps professionals. Over the course of controlled simulation runs, quantitative data like as build times, deployment latencies, and failure rates were gathered. On the other hand, practitioner input was gathered through interviews and questionnaires. According to the findings, the optimized pipeline was able to achieve a reduction of 32.87% in the average build time, a reduction of 34.02% in deployment latency, and a reduction of over 51% in failure rates. Although initial setup complexity was highlighted, thematic analysis of practitioner comments indicated gains in build efficiency, fault isolation, and deployment control. However, the complexity of the initial setup was noted. The findings of the study indicate that the proposed improvements considerably improve the performance and reliability of continuous integration and continuous delivery pipelines in microservice environments. This provides a real benefit for contemporary DevOps processes when implemented.